2018
DOI: 10.1371/journal.pone.0193343
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid antagonizes the boosting effect of palmitic acid on LPS inflammatory signaling by inhibiting gene transcription and ceramide synthesis

Abstract: It is well known that saturated fatty acids (SFAs) and unsaturated fatty acid, in particular omega-3 polyunsaturated fatty acids (n-3 PUFAs), have different effects on inflammatory signaling: SFAs are pro-inflammatory but n-3 PUFAs have strong anti-inflammatory properties. We have reported that palmitic acid (PA), a saturated fatty acid, robustly amplifies lipopolysaccharide (LPS) signaling to upregulate proinflammatory gene expression in macrophages. We also reported that the increased production of ceramide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Thus, macrophage function and phenotype are highly dependent on their microenvironment [40]. Lipids (cellular or dietary) and alterations in lipid metabolism have long been identified as regulators of immune cell function and macrophage polarization [27,[41][42][43][44]. Consistent with previous reports, our data demonstrate that PA and Cer attenuate the M2-phenotype in macrophages.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, macrophage function and phenotype are highly dependent on their microenvironment [40]. Lipids (cellular or dietary) and alterations in lipid metabolism have long been identified as regulators of immune cell function and macrophage polarization [27,[41][42][43][44]. Consistent with previous reports, our data demonstrate that PA and Cer attenuate the M2-phenotype in macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…Albeit being different lipid species, PA and Cer block M2-TAM polarization. Previous studies demonstrated that Cer is synthesized upon PA-amplified LPS-signaling, and stimulates the transcription of pro-inflammatory cytokines [43,47]. Thus, it is likely that addition of Cer, a downstream signaling mediator of PA-mediated TLR signaling, directly stimulates the same pro-inflammatory response as PA.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that palmitic acid is related to a higher risk of death from CVD. Palmitic FA, by enhancing inflammation-related signaling of lipopolysaccharides in macrophages, promotes inflammation and the development of CVD [34][35][36]. In addition, inflammatory activity probably is characterized by increased production of pro-inflammatory cytokines and oxidants, leading to cellular hypertrophy and apoptosis.…”
Section: The Notation Of Fatty Acid (Number Of Carbon Atoms: Number πmentioning
confidence: 99%
“…In bovine primary adipocyte cultures, Rico et al (2018) reported that ceramides are involved in the inhibitory pathway of insulin-stimulated glucose uptake through the downregulation of protein kinase B, AKT. While the exact mechanism by which palmitoleic acid could reduce ceramide synthesis is not known, we hypothesize that it can exert similar ceramidelowering effects similar to other MUFA like oleic acid (Jin et al, 2018). Oleic acid reduces ceramide accumulation with the simultaneous induction of mitochondrial FA oxidation and the reduction of inflammatory signals, both of which can improve insulin signaling (Palomer et al, 2018).…”
Section: Discussionmentioning
confidence: 96%